Protected areas, ecotourism, and gateway communities: economic analysis of the Monarch Butterfly Sanctuary, Michoacan, Mexico - Kido, Antonio, author (Colorado State University. Libraries, 2004)
Although conservation policies and practices have always been influenced by political and economic factors, economic analysis has played a limited role in conservation decision-making until recent years. Many people are realizing that the fundamental forces driving the loss of biological diversity (e.g. land conversion and over-exploitation of natural parks) have economic roots. Economics is concerned with the allocation of scarce resources among competing human wants and can provide especially useful tools for addressing conservation issues. This dissertation describes an economic analysis with emphasis on the distribution of benefits among stakeholders derived from the sanctuary of the monarch butterfly in Mexico. Economic valuation is presented and contrasted by two related techniques for measuring recreational demand, and welfare measures are derived from these techniques. People's price response to higher fees versus higher travel costs is also analyzed. The magnitude of local economic impact from tourism spending and multiplier effects is explored. Finally, policy scenarios that provide potential solutions depending on the account stance of the analyst and the attribution of property rights are investigated.
Keywords: recreation; wildlife conservation; butterflies and moths; studies; public access; values; federal government; community; wilderness areas; parks and recreation areas; local government; objectives; property rights; tourism; ecotourism; nature; natural resource management; hypotheses; low income groups; environmental protection; biosphere; national parks; fees and charges